Effects of composition, grinding, and heat treatment on the coloration of alkali borosilicate glasses - Yuto Okawara; Koji Kawada; Yuuka Kokubo; Aiko Shimada; Yuta Nishina; Koji Yazawa; Kenzo Deguchi; Shinobu Ohki; Rei Okuno; Hirofumi Inada; Taigo Takaishi; Toshinori Okura; et al. (Next Research, 2025)

Lactoferrin and its digestive peptides induce interferon-α production and activate plasmacytoid dendritic cells ex vivo - Shutaro Kubo; Momoko Miyakawa; Asuka Tada; Hirotsugu Oda; Hideki Motobayashi; Sadahiro Iwabuchi; Shinobu Tamura; Miyuki Tanaka; Shinichi Hashimoto (BioMetals, 2023)
Plasmacytoid dendritic cells (pDCs) recognise viral single-stranded RNA (ssRNA) or CpG DNA via Toll-like receptor (TLR)-7 and TLR9, and produce interferon (IFN)-α. Activated pDCs upregulate human leukocyte antigen (HLA)-DR and CD86 expression levels. Ingestion of bovine lactoferrin (LF) activates pDCs, but little is known about its effects. In this study, the effects of LF and its pepsin hydrolysate (LFH) on the production of IFN-α from peripheral blood mononuclear cells (PBMCs) and pDCs were examined. PBMCs were prepared from peripheral blood of healthy adults and incubated with LF, LFH, or lactoferricin (LFcin) in the absence or presence of ssRNA derived from human immunodeficiency virus. The concentration of IFN-α in the supernatant and the expression levels of IFN-α, HLA-DR, and CD86 in pDCs were quantified by enzyme-linked immunosorbent assay and flow cytometry. In the absence of ssRNA, the concentration of IFN-α was negligible and LF had no effect on it. In the presence of ssRNA, IFN-α was detected at a certain level, and LF and LFH significantly increased its concentration. The increase caused by LFH and LFcin were comparable. In addition, LF significantly upregulated the expression levels of IFN-α, HLA-DR, and CD86 in pDCs. LF and its digestive peptides induced IFN-α production and activated pDCs in the presence of ssRNA, suggesting that LF modulates the immune system by promoting pDC activation upon viral recognition.

Gender differences in the effects of job insecurity on psychological distress in Japanese workers: a population-based panel study - Yuko Kachi; Hideki Hashimoto; Hisashi Eguchi (International Archives of Occupational and Environmental Health, 2018)

How do surrounding environments influence the electronic and vibrational properties of spheroidene? - Noriyuki Tonouchi; Daisuke Kosumi; Mitsuru Sugisaki; Mamoru Nango; Hideki Hashimoto (Photosynthesis Research, 2015)

Light-dependent conformational change of neoxanthin in a siphonous green alga, Codium intricatum, revealed by Raman spectroscopy - Chiasa Uragami; Denise Galzerano; Andrew Gall; Yusuke Shigematsu; Maïwen Meisterhans; Naohiro Oka; Masahiko Iha; Ritsuko Fujii; Bruno Robert; Hideki Hashimoto (Photosynthesis Research, 2014)

Characterization of the intramolecular transfer state of marine carotenoid fucoxanthin by femtosecond pump–probe spectroscopy - Daisuke Kosumi; Ritsuko Fujii; Mitsuru Sugisaki; Naohiro Oka; Masahiko Iha; Hideki Hashimoto (Photosynthesis Research, 2014)

Functional and occupational characteristics predictive of a return to work within 18 months after stroke in Japan: implications for rehabilitation - Hirotaka Tanaka; Toshihiro Toyonaga; Hideki Hashimoto (International Archives of Occupational and Environmental Health, 2014)

The 10th International Conference on EcoBalance (EcoBalance 2012)—Challenges and Solutions for Sustainable Society, November 20–23, 2012, Tokyo, Japan - Shigeyuki Miyamoto; Toshiharu Ikaga; Minako Hara; Shun Kawakubo; Yasunari Matsuno; Kenichi Nakajima; Kiyoshi Dowaki; Masaharu Motoshita; Kiyotada Hayashi; Kazuyo Matsubae; Michiyasu Nakajima; Hideki Kakisawa; et al. (The International Journal of Life Cycle Assessment, 2013)

Generation of gene-targeted mice using embryonic stem cells derived from a transgenic mouse model of Alzheimer’s disease - Satoshi Yamamoto; Yuki Ooshima; Mitsugu Nakata; Takashi Yano; Kunio Matsuoka; Sayuri Watanabe; Ryouta Maeda; Hideki Takahashi; Michiyasu Takeyama; Yoshio Matsumoto; Tadatoshi Hashimoto (Transgenic Research, 2013)

The pigment stoichiometry in a chlorophyll a/c type photosynthetic antenna - Ritsuko Fujii; Mamiko Kita; Matsumi Doe; Yoshiro Iinuma; Naohiro Oka; Yuki Takaesu; Tomonori Taira; Masahiko Iha; Tadashi Mizoguchi; Richard J. Cogdell; Hideki Hashimoto (Photosynthesis Research, 2012)

Isolation and purification of the major photosynthetic antenna, fucoxanthin-Chl a/c protein, from cultured discoid germilings of the brown Alga, Cladosiphon okamuranus TOKIDA (Okinawa Mozuku) - Ritsuko Fujii; Mamiko Kita; Yoshiro Iinuma; Naohiro Oka; Yuki Takaesu; Tomonori Taira; Masahiko Iha; Richard J. Cogdell; Hideki Hashimoto (Photosynthesis Research, 2012)

Impact of medium volume and oxygen concentration in the incubator on pericellular oxygen concentration and differentiation of murine chondrogenic cell culture - Hiroki Oze; Makoto Hirao; Kosuke Ebina; Kenrin Shi; Yoshitaka Kawato; Shoichi Kaneshiro; Hideki Yoshikawa; Jun Hashimoto (In Vitro Cellular & Developmental Biology - Animal, 2012)

Isolation of a Leptothrix Strain, OUMS1, from Ocherous Deposits in Groundwater - Michinori Sawayama; Tomoko Suzuki; Hideki Hashimoto; Tomonari Kasai; Mitsuaki Furutani; Naoyuki Miyata; Hitoshi Kunoh; Jun Takada (Current Microbiology, 2011)

First capture of post-spawning female of the Japanese eel Anguilla japonica at the southern West Mariana Ridge - Hiroaki Kurogi; Makoto Okazaki; Noritaka Mochioka; Tadao Jinbo; Hiroshi Hashimoto; Masanori Takahashi; Atsushi Tawa; Jun Aoyama; Akira Shinoda; Katsumi Tsukamoto; Hideki Tanaka; Koichiro Gen; et al. (Fisheries Science, 2011)

Molecular assembly of Zn porphyrin complexes using synthetic light-harvesting model polypeptides - Tsuyoshi Ochiai; Takahide Asaoka; Tomoya Kato; Shinichiro Osaka; Takehisa Dewa; Keiji Yamashita; Alastair T. Gardiner; Hideki Hashimoto; Mamoru Nango (Photosynthesis Research, 2008)

Mimicking the photosynthetic system with strong hydrogen bonds to promote proton electron concerted reactions - Isamu Kinoshita; Hideki Hashimoto; Takanori Nishioka; Riichi Miyamoto; Naoto Kuwamura; Yuki Yoshida (Photosynthesis Research, 2008)

Four-wave mixing signals from β-carotene and its n = 15 homologue - Mitsuru Sugisaki; Masazumi Fujiwara; Kazuhiro Yanagi; Richard J. Cogdell; Hideki Hashimoto (Photosynthesis Research, 2008)

Construction of hybrid photosynthetic units using peripheral and core antennae from two different species of photosynthetic bacteria: detection of the energy transfer from bacteriochlorophyll a in LH2 to bacteriochlorophyll b in LH1 - Ritsuko Fujii; Shozo Shimonaka; Naoko Uchida; Alastair T. Gardiner; Richard J. Cogdell; Mitsuru Sugisaki; Hideki Hashimoto (Photosynthesis Research, 2008)

Linear and nonlinear optical responses in bacteriochlorophyll a - Mitsuru Sugisaki; Ritsuko Fujii; Richard J. Cogdell; Hideki Hashimoto (Photosynthesis Research, 2008)

Electrostatic effect of surfactant molecules on bacteriochlorophyll a and carotenoid binding sites in the LH1 complex isolated from Rhodospirillum rubrum S1 probed by Stark spectroscopy - Katsunori Nakagawa; Satoru Suzuki; Ritsuko Fujii; Alastair T. Gardiner; Richard J. Cogdell; Mamoru Nango; Hideki Hashimoto (Photosynthesis Research, 2008)

Probing binding site of bacteriochlorophyll a and carotenoid in the reconstituted LH1 complex from Rhodospirillum rubrum S1 by Stark spectroscopy - Katsunori Nakagawa; Satoru Suzuki; Ritsuko Fujii; Alastair T. Gardiner; Richard J. Cogdell; Mamoru Nango; Hideki Hashimoto (Photosynthesis Research, 2008)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Effects of shift work on QTc interval and blood pressure in relation to heart rate variability - Katsuyuki Murata; Eiji Yano; Hideki Hashimoto; Kanae Karita; Miwako Dakeishi (International Archives of Occupational and Environmental Health, 2005)

Purple Bacterial Light-harvesting Complexes: From Dreams to Structures - Richard J. Cogdell; Hideki Hashimoto; Alastair T. Gardiner (Photosynthesis Research, 2004)

Carotenoids and bacterial photosynthesis: The story so far... - Niall J. Fraser; Hideki Hashimoto; Richard J. Cogdell (Photosynthesis Research, 2001)

Differential effects of bacterial toxins on mitogenic actions of sodium fluoride and those of aluminum fluoride in human TE85 osteosarcoma cells - Hideki Hashimoto; K.-H. William Lau (Molecular and Cellular Biochemistry, 2001)

Electrokinetic phenomena associated with a water injection experiment at the Nojima fault on Awaji Island, Japan - Hideki Murakami; Takeshi Hashimoto; Naoto Oshiman; Satoru Yamaguchi; Yoshimori Honkura; Norihiko Sumitomo (Island Arc, 2001)

Electrokinetic phenomena associated with a water injection experiment at the Nojima fault on Awaji Island, Japan - Hideki Murakami; Takeshi Hashimoto; Naoto Oshiman; Satoru Yamaguchi; Yoshimori Honkura; Norihiko Sumitomo (Island Arc, 2001)
Self‐potential variations were measured to estimate the magnitude of electrokinetic and hydrological parameters (zeta potential and permeability) of the Nojima Fault zone in Awaji, Japan. The study observed self‐potential variations that seemed to be associated with water flow from the injection well to the fracture zone, which were induced by turning the injection on and off. Amplitudes of the variations were a few to 0.03 V across 320–450 m dipoles. These variations can be explained well with an electrokinetic model. The quantity k/ζ (permeability/zeta potential) is in the range 1.6 × 10 −13 − 5.4 × 10 −13 m 2 /V. Permeability of the Nojima fault zone can be estimated as approximately 10 −16 –10 −15 m 2 on the assumption that the zeta potential is in the range –0.01 to –0.001 V.

Cell proliferation and death of Hertwig's epithelial root sheath in the rat - Hiroyuki Kaneko; Sadamitsu Hashimoto; Yasunobu Enokiya; Hideki Ogiuchi; Masaki Shimono (Cell and Tissue Research, 1999)